2011
DOI: 10.1108/10222521111178628
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reporting and assurance

Abstract: PurposeThe purpose of this paper is to provide an overview of sustainability reporting and the assurance thereof in South Africa.Design/methodology/approachThe paper takes the form of a literature review and a study of empirical evidence obtained through content analysis of the sustainability reports of companies listed on the Johannesburg Securities Exchange Socially Responsible Investment Index for 2009.FindingsAlthough sustainability reporting and the independent assurance thereof are widely researched and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…As reported in Exhibit 4, there are only 16 reports in the sample that were accompanied by an opinion from an external assurance provider. This finding is in line with other studies that found external assurance of sustainability reports to be limited in emerging markets due to its costliness (Darus et al, ; Marx & van Dyk, ). In my sample, Big Four accounting firms produced the majority of the assurance reports (12 of the 16 reports), while the British Standards Institution (BSI) prepared the other 4 reports.…”
Section: Reliance On External Assurance Providerssupporting
confidence: 92%
“…As reported in Exhibit 4, there are only 16 reports in the sample that were accompanied by an opinion from an external assurance provider. This finding is in line with other studies that found external assurance of sustainability reports to be limited in emerging markets due to its costliness (Darus et al, ; Marx & van Dyk, ). In my sample, Big Four accounting firms produced the majority of the assurance reports (12 of the 16 reports), while the British Standards Institution (BSI) prepared the other 4 reports.…”
Section: Reliance On External Assurance Providerssupporting
confidence: 92%
“…practitioners. Research on the motivations for reporting (Buhr, 2007;Deegan, 2007;Bebbington et al 2009), the content of reports (Perrini, 2005;Stiller & Daub, 2007;Sobhani et al, 2009;Kolk and Pinske, 2010;Morhardt, 2010), report verification (O'Dwyer & Owen, 2005;Simnett et al 2009;Jones & Solomon, 2010;Kolk & Perego, 2010;O'Dwyer et al, 2011) and the process of reporting (Adams, 2002;Adams & McNicholas, 2007;Adams & Frost, 2008) is well established. Corporations are increasingly reporting on their sustainability initiatives and recent work shows that the great majority of the world's largest companies now engage in some form of sustainability reporting (KPMG, 2011).…”
Section: Orporate Sustainability Reporting Has Received a Great Deamentioning
confidence: 99%
“…Guenther et al analyzed environmental reporting of global mining, gas and oil companies and found a big gap when it comes to quantity versus quality of disclosure [48]. In Canada, it was found that CSR reporting quality in the mining industry is only slightly over 25%, trailing behind other industries [83]. In addition, Fonseca et al, in their research findings on sustainability reporting among mining corporations, point out critical limitations in the GRI approach [100].…”
Section: Discussionmentioning
confidence: 99%
“…The assumption behind this quantitative content analysis is that volume signifies importance. Several authors [33,[83][84][85] argued that using sentences would be a better variable to use but it was found that the use of words was more appropriate for this study as individual words included in graphs, tables, etc., could also be taken into account. This assumption is consistent with Deegan and Gordon that argue that by doing so the disclosure level can be measured in more detail [86].…”
Section: Independent Variablesmentioning
confidence: 99%